Peningkatan Literasi Digital Pemanfaatan Qris pada Pelaku UMKM di Desa Pesisir Pantai: Pengabdian - Sri Prilmayanti Awaluddin; Murtiadi Awaluddin; Yuli Rahmini Suci; Asriani; Muhammad Zul Fahmi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program aims to improve digital literacy among MSME actors in Kassi Village, Jeneponto Regency, particularly in the use of QRIS and digital marketing. MSME actors in this area often face limitations in accessing digital technology that can enhance their business efficiency and competitiveness. The training provided includes an introduction to QRIS as a digital payment system that facilitates transactions, as well as digital marketing techniques through social media and e-commerce platforms. The training results showed a significant increase in MSME actors’ knowledge of QRIS, from 45% in the pre-test to 85% in the post-test. In addition, skills in digital marketing also improved significantly, with more than 60% of MSME actors actively using social media to market their products. The use of QRIS has also accelerated transactions and reduced dependence on cash payments. The implementation of digital marketing has expanded the market reach of local products, which were previously limited to only local markets. Increasing digital literacy (QRIS and marketing) increases efficiency and expands the MSME market, creating more sustainable opportunities.